2017
DOI: 10.1007/s12053-017-9555-y
|View full text |Cite
|
Sign up to set email alerts
|

Watts your usage? A field study of householders’ literacy for residential electricity data

Abstract: Smart metering studies typically focus on quantifying behavior change. However, little is known about how users understand energy information and analyze and interpret feedback from energy data visualizations. To investigate this, we gave 13 participants from nine UK households an electricity power clamp meter. Prior to installing and using the device, we conducted interviews with participants to gauge their understanding of their home electricity consumption and found that participants varied considerably fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 42 publications
(46 reference statements)
0
18
1
Order By: Relevance
“…The research objective was to inquire how people make sense of and reflect on energy data. In contrast to earlier work, our study found that participants did rather well in terms of explaining their data patterns: Overall, annotations were plausible which is in contrast with the field study interviews by Herrmann et al (2018), who concluded that householders perform rather poorly in making sense of their energy data when presented as a time series line graph. The core difference between the two studies is that thanks to FigureEnergy as an interactive prototype, in our study participants could annotate and hence actively reflect on their data patterns as often as they wanted, and they were encouraged to do so.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The research objective was to inquire how people make sense of and reflect on energy data. In contrast to earlier work, our study found that participants did rather well in terms of explaining their data patterns: Overall, annotations were plausible which is in contrast with the field study interviews by Herrmann et al (2018), who concluded that householders perform rather poorly in making sense of their energy data when presented as a time series line graph. The core difference between the two studies is that thanks to FigureEnergy as an interactive prototype, in our study participants could annotate and hence actively reflect on their data patterns as often as they wanted, and they were encouraged to do so.…”
Section: Discussioncontrasting
confidence: 99%
“…The aim of this exploratory field study Energy Efficiency is to gain insights into householders' ability to make sense of their consumption data, when given the opportunity to actively engage with it and reflect on it over the course of several days or weeks. This is in extension to existing research which shows limited ability in householders to explain their data spontaneously (Herrmann et al, 2018). Before describing this study in detail, we first give a brief description of FigureEnergy.…”
Section: Related Workmentioning
confidence: 91%
See 1 more Smart Citation
“…Microgrids are not passive networks of electrical currents but are dynamic systems that are as responsive to the elements that power them as they are to the actors who use them. From an economic perspective, electricity is a commodity that is traded, bought and sold, but an everyday user may perceive it is an unintuitive, intangible good that must be used immediately and cannot be stored [6]. Consequently, users are not intrinsically reflective of the implications of their consumption patterns and will not reflexively alter these patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The process of decarbonizing the economy will depend, to some extent, on the demand-side flexibility, which may be fostered through the use of time-differentiated tariffs, either with static and dynamic options [1]. In these pricing schemes, end-users are encouraged to adopt more flexible consumption patterns, adjusting their demand profile by reducing or increasing consumption in different time periods, shifting load operation to cheaper time periods or redefining thermostat settings [2], [3]. According to [2] and [4], some factors may influence end-users' enrolment in DR programs, such as: end-user's energy literacy level; the complexity of DR programs and dynamic tariffs; technology costs (when compared to savings and incentives provided); the effort required to search for dynamic pricing information and adjust electrical appliances usage accordingly; risk/loss aversion; and the inertia associated with behavioral change.…”
Section: Introductionmentioning
confidence: 99%